Pelatihan Pemasaran Produk menggunakan E-Marketing sebagai Solusi untuk Menghadapi Dampak Virus COVID-19 bagi Pedagang Kaki Lima di Kota Surakarta - Christiana Shinta Indhiarti; Silvia Melinda Oktaviani; Luki Eko Wahyudi; Eskasari Putri (Prosiding University Research Colloquium, 2020)
Community dedication by the University of Muhammadiyah Surakarta aims to improve the welfare of the community, especially street vendors in Surakarta who are also affected by the current Covid-19 pandemic. Through an increased understanding of the use of the latest technology in product marketing, it is hoped that it can help the continuity of street vendors. The general benefit of this community dedication is to provide e-marketing training to street vendors in Surakarta City in marketing their products during the Covid-19 pandemic. Benefits community dedication directed for business continuity during the Covid-19 so that the standard of living and well-being public resolved. Training methods use lectures, training, and discussion. The training method emphasizes the practice of its application namely how to operate social media applications and market products on the platform using appropriate technology. The training will be conducted for six months. If a training activity has a good impact on the community, especially street vendors, there will be follow-up and other cooperation in a more academic direction.